(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
As with other ichnofossils, the study of the ichogenus Entobia Bronn, 1837, attributed to the activity of boring sponges, is useful to understand taphonomic processes and reconstruct paleoenvironments. Here we delineate a diverse Entobia assemblage from Sicily, the first described from this Mediterranean island, based on the discovery of well-preserved natural casts. The studied association is represented by seven ichnotaxa, Entobia cateniformis, E. cateniformis form A, E. geometrica, E. laquea, E. ?megastoma, E. ovula, E. ?paradoxa, which come from the late Caenozoic sites of Altavilla Milicia and Sferracavallo, in north-western Sicily. Aragonitic bivalves, mostly veneroids, served as substrate for the boring organisms responsible of producing these ichnotaxa. Entobia was also found associated with natural casts of the boring Caulostrepsis taeniola, produced by polychaetes. Ichnology and shell-bed taphonomy indicates that investigated deposits formed in conditions of low rate of sedimentation; post depositional processes involved chemical conditions favorable to the preservation of calcite shells.